Factors related to mortality in patients with severe burns treated in the severe burn unit at Hubert Koutoukou MAGA national university hospital of Cotonou - HOUNKPE, PIERRE-CLAVER; Boukari, BM; AKPADJAN, GBEMAWONMEDE FABRICE; AHOUNOU, Ernest; Whannou, P; ADEGBIDI, Hugues; Atadokpèdé, Félix (My University, 2019)
ABSTRACT Burn injuries are a global scourge, responsible for more than 265,000 deaths per year, especially in low-income countries that account for 95% of all burned patients; among them, children are 70%. Burned patients in African countries are a real public health problem; however, they are not yet among the health priorities of these countries. In Benin, they represent a real public health concern. Goal: Determine the predictive factors most significantly associated with the mortality in burned patients in the severe burn unit at CNHU-HKM in Cotonou. Methods: This is a retrospective study between half, 2011 and 1st half, 2017. The study population included all the deceased severe burned patients during the study period. The variables studied are: the intrinsic data of the patients, anamnestic data, physical examination data at admission and the care data of the care. The data collected was entered into a database and the statistical analysis was carried out using Epi info software. Results: Overall, 81 patients deceased among 246 hospitalizations. So the mortality rate was 32.9%. 10 patients (12.3% of deaths) died within 48 hours of the accident. 34 patients (42%) died between the third and seventh days and 37 patients (45.7% of deaths) died after the seventh day following the accident. The average delay of death is 15.9 days. Mortality rates are in the extreme age groups: respectively 36.40% and 72.73% in age groups less than or equal to 4 years and greater than or equal to 60 years. 50.6% of the deaths are female and 49.4% are male. The predictive factors significantly associated with the mortality were: Age ≥ 60 years, the pathology history; a mechanical ventilation procedure, a stay in intensive care unit; a BBS>50%; the attainment of functional areas; a fuel inflammation burn; an index of leases>75; hypovolemic shock; hypoprotidemia; Ionic disorders and Sepsis. Conclusion: Burning accidents are very common in Benin. Mortality is high. The many factors associated with this mortality include: Age>60 years, comorbidity, gasoline inflammation, burned body surface area greater than 50%, ionic disorders and sepsis.
Keywords: Severe burn patients; Mortality; Relative risk; Associated factors; CNHU-HKM in Cotonou